Study on the Influence of Inter Turn Short Circuit Fault on Permanent Magnet Synchronous Motor Output Performance. Issue 9 (28th May 2018) - Qiu, Hongbo; Hu, Kaiqiang; Yu, Wenfei; Tang, Bingxia; Wang, Wei; Yang, Cunxiang
Abstract: When the inter turn short circuit (ITSC) fault occurs, the value of the short circuit ring loop current is large. A pulsating magnetic field generated by the loop current has a great influence on the motor inside magnetic field. The motor internal magnetic field is obviously distorted, and the motor output performance is limited. In order to study the influence of the fault on the permanent magnet synchronous motor (PMSM) output performance, first, a PMSM fault model is established based on the FEM. The influence of the fault on the motor electromagnetic field is studied. The motor magnetic field is decoupled and the armature magnetic field harmonic content is obtained by using the Fourier decomposition theory. Second, by using the Maxwell energy method, the output torque, radial force density and electromagnetic force are analyzed. The influence mechanism of the ITSC fault on the torque ripple and the electromagnetic force is revealed. Finally, the prototype test platform is built to study the ITSC fault, and the simulation results are compared with the experimental data. The correctness of simulation research is verified. The conclusions obtained are of the great significance for the PMSM fault analysis.